PHQ-9 and PHQ-2 for Screening Depression in Chinese Rural Elderly. - Zi-Wei Liu; Yu Yu; Mi Hu; Hui-Ming Liu; Liang Zhou; Shui-Yuan Xiao (PLoS ONE, 2016)
Objectives This study aimed to explore cut-off scores of the 9-item Patient Health Questionnaire (PHQ-9) and 2-item Patient Health Questionnaire (PHQ-2) for depression screening in Chinese rural elderly. Methods A cross-sectional study was conducted on 839 residents aged 60 years and above in rural areas of Liuyang County. PHQ-9 was adopted to evaluate depression. The Structured Clinical Interview for DSM Disorders (SCID-I) was adopted to diagnose major depressive disorder (MDD) as a golden standard. Sensitivity, specificity, positive and negative predictive value, positive and negative likelihood ratio, Youden's index and the receiver operating characteristic (ROC) curve were analyzed on PHQ-9 and PHQ-2. Results The Cronbach's alphas of PHQ-9 and PHQ-2 were 0.82 and 0.76, respectively. The score of 8 of the PHQ-9 showed the highest Youden's index of 0.85, with a sensitivity of 0.97 and specificity of 0.89 respectively, and the area under the ROC curve (AUC) was 0.97 (95% CI: 0.96-0.98). The score of 3 of PHQ-2 showed the highest Youden's index of 0.79, with both sensitivity and specificity were 0.90 and the AUC was 0.94 (95% CI: 0.90-0.97). Conclusions Both PHQ-9 and PHQ-2 are valid screening instruments for depression in the rural elderly in China, with recommended cut-off scores of 8 and 3 respectively.